Competitiveness: A systematic review of e-commerce and social media strategies for micro, small, and medium enterprises (MSMEs) - Irfan, Mohamad (ARKA INSTITUTE, 2025)
In the digital economy era, the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) is crucial for national economic resilience and growth. The adoption of digital technology, particularly e-commerce and social media, has become a critical factor in facing disruption and global competition. This research aims to synthesize empirical evidence from the last five years regarding strategies for enhancing MSME competitiveness through the adoption of e-commerce and social media. The study employs a Systematic Literature Review (SLR) method. Literature searches were conducted in indexed databases such as Google Scholar, ScienceDirect, Scopus, and Emerald Insight using the keywords